AN OVERVIEW OF CERVICAL CANCER KNOWLEDGE AND SCREENING AMONG FEMALE HEALTHCARE PRACTITIONERS - Kamberi, Fatjona; Theodhosi, Gjergji; Bilushi, Yllka; Cuberi, Diana; Sinaj, Enkeleda (European Scientific Journal, ESJ, 2014)
In Albania, cervical cancer (CC) is diagnosed in late stage with high prevalence of deaths. Little is known about the knowledge and barriers that women in general and female Healthcare Practitioners (HCPs) in particular have about it and its screening. The aim of this cross-sectional study is to assess the CC knowledge and screening among female (HCPs) in primary healthcare services and hospital, and whether differences exist between them. A standardized, structured self-administered questionnaire was used for the data collection in 116 female HCPs in Vlora city in March 2014, 67 female HCPs in primary health care services and 49 in hospital. Descriptive statistic was used for the data analysis. The study evidenced that all of HCPs in the study knew of CC. Most of them knew the association of CC and human papillomavirus infection. All agree the fact that cervical cancer is preventable. A good percentage of HCPs had knowledge of the Pap smear, but a half of them knew that it is used for the screening of CC. A small percentage of HCPs had ever had a pap smear. The results of the study indicated that there are no major differences among female HCPs. This study evidenced the need for nurses and female HCPs in general to enhance knowledge regarding cervical screening in both primary and hospital services. The study evidenced a series of barriers to effective screening services.